Content intelligence technology: A business transformation tool in emerging economies. Issue 6 (18th August 2022) - Jain, Manjula; Gupta, Sandeep; Gupta, Shilpi; Pandey, Mayank Kumar
Abstract: Business organizations are implementing various advanced technologies viz. computing, software and storage for improving the understanding of their content to enable them to undertake effective business decisions. Business organizations in the emerging economies are rapidly searching for technologies with enhanced service capabilities that could be leveraged throughout organizations. Whether structured or unstructured, content organizations aim at extracting relevant information from wide range of content and the amalgamation of artificial intelligence, internet of things and machine learning technologies supports the companies to achieve this objective. Across the globe, it has been estimated that Asia-Pacific is creating ample opportunities for content intelligence technique to flourish and witness high growth rate. The paper attempts to explore the possibility of how content intelligence is transforming business processes in the emerging economies. Additionally, it aims at delivering detailed insight into the trends and driving forces towards the growth of content intelligence technique in emerging economies.